A Fatal Case of Louping-ill in a Dog: Immunolocalization and Full Genome Sequencing of the Virus. (November 2018) - Dagleish, M.P.; Clark, J.J.; Robson, C.; Tucker, M.; Orton, R.J.; Rocchi, M.S.
Summary: Louping-ill (LI), caused by louping-ill virus (LIV), results in a frequently fatal encephalitis primarily affecting sheep and red grouse ( Lagopus lagopus scotica ), but it does occur in other species. An adult male Border collie dog was definitively diagnosed with fatal LI and the lesion profile, LIV antigen distribution and full genome sequence of the LIV responsible were investigated to determine if this differed significantly from sheep-derived LIV. No gross lesions were present. The histological lesions were confined to the central nervous system and comprised of lymphocytic perivascular cuffs, glial foci, neuronal necrosis and neuronophagia. Immunolocalization of viral antigen showed small amounts present in neurons only. These histological and immunohistochemical findings were similar to those reported in affected sheep. Compared with published full genome sequences of sheep-derived LIV, only very minor differences were present and phylogenetically the virus clustered individually between a subclade containing Scottish strains, LIV 369/T2 and G and another subclade containing an English isolate LIV A. The LIV isolated from the dog shares a common progenitor with LIV A. These findings suggest there is no canine-specific LIV strain, dogs are susceptible to sheep-associated strains of LI and with the increase in tick prevalence, and therefore exposure to LIV, a safe, effective vaccine for dogs may be required.